Model of Factors Lasting Achievement of Excellent Results (Journal of Universal Excellence, 2026)
Research Question (RQ): In the survey, we will mainly deal with the question of how to ensure the continued achievement of excellent results in an organization.Purpose: The main purpose and goal of the research is to present a model or standard on the basis of literature, which help us achieve our goal, in order to achieve excellent results. Permanent achievement of excellent results can be guaranteed by different standards. The most common are the ISO standard and the EFQM standard.Method: A qualitative benchmarking method is used, based on the analysis of various articles by domestic authors.Results: The results show that there are many different standards that companies can use to achieve excellent results in their own organization and on the market. We also found that the introduction of the standard into the company and the condition that it will be successful, but the whole company must strive to lead the best from the bottom to achieve the best possible results and to maintain a culture of relations between themselves and the outside.Organization: If the leaders in different organizations followed the model of excellence, the organization would have even better developed and it would be a gain for the organization.Society: Comparisons can be used in the wider environment and help them on the road to excellence.Originality: The study describes models of factors for the continued achievement of excellent results.Limitations/Future Research: further research can be extended to a concrete organization that does not yet have established standards of excellence.
Keywords: sustainability; achievement; results; EFQM standard; excellence; model